Assédio moral no ambiente de trabalho e seus impactos na saúde mental - Ana Paula de Figueiredo; Oldair Donizete Galeni; Mariana Fabricio Rezende; Mara Lucia Resende Silva; Neuzilene da Silva Ximenes; Claudio Henrique Pereira; Camila Santos Pereira; Andrea Cristina Rocha; Patricia Ferreira Batista; Divania Aparecida Santos Eugênio (Revista ft, 2026)
Workplace bullying is an important occupational health problem characterized by abusive practices that can compromise workers' dignity, professional relationships, and psychological well-being. Exposure to humiliation, embarrassment, intimidation, isolation, professional disqualification, and other forms of psychological violence may have significant consequences for mental health, contributing to emotional distress, anxiety, depressive symptoms, occupational stress, exhaustion, and impaired quality of life. This study aims to analyze workplace bullying and its impacts on workers' mental health, discussing associated factors, individual and organizational consequences, and prevention and coping strategies. This is a narrative literature review with a qualitative and descriptive approach, based on scientific publications and institutional documents related to mental health, occupational health, psychosocial risks, and workplace violence. The literature indicates that organizational environments characterized by authoritarian relationships, inadequate communication, excessive competition, weak institutional support, and tolerance of abusive behaviors may contribute to workplace bullying. It is concluded that addressing this phenomenon requires permanent organizational measures, institutional prevention policies, safe communication channels, leadership training, and the strengthening of work environments based on respect, dignity, and protection of mental health.